Penerapan Ultrasonik dalam Penelitian Aktivitas Antibakteri Staphylococcus epidermidis Ekstrak Daun Kelor (Moringa oleifera): Pendekatan Berbasis Sains dan Nilai Islam - Tiyas, Rika Setianing; Yulianti, Eny; Fahruddin, Muhammad Mukhlis (UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG, 2024)
This study reveals the potential of ultrasonic extraction method in yielding valuable extracts from Moringa oleifera leaves. Moringa oleifera, a versatile plant, takes center stage in this research. The concept aligned with the teachings of the Quran regarding the intricacies of Moringa and its application in acne treatment offers a secure and sustainable option. The utilization of ultrasonic extraction technique contributes to enhancing the benefits obtainable from Moringa. The antibacterial properties identified within Moringa position it as a promising candidate within the realm of medical applications, thereby aligning with the values propagated by the Quran, emphasizing the appreciation of nature's wonders.The methodology of this research involves ultrasonic extraction method and phytochemical analysis conducted in a laboratory setting, alongside evaluating the antibacterial potential through literature review. A bibliometric approach is employed to analyze relevant literature and Quranic verses concerning Moringa. This research falls within the qualitative research category and embodies the post-positivist perspective. Findings of the study indicate that the ultrasonic extraction method successfully yields approximately 22.22% of extract. Moreover, the phytochemical analysis reveals the presence of compounds such as flavonoids, saponins, tannins, alkaloids, triterpenoids, and steroids in the ethanol extract of Moringa leaves.